2017
DOI: 10.1111/odi.12708
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for medication‐related osteonecrosis of the jaws: A systematic review

Abstract: The purpose of this study was to identify the patient populations at risk of medication-related osteonecrosis of the jaw (MRONJ) and determine which medical and dental comorbidities are significant risk factors for this disease. An electronic search of Embase, MEDLINE, Cochrane Central Register of Controlled Trials, WHO International Clinical Trials Registry Platform and ProQuest Dissertations and Theses Global was conducted to identify all human studies that reported risk factors for MRONJ. Only a qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
199
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(212 citation statements)
references
References 29 publications
4
199
2
7
Order By: Relevance
“…Currently, the effectiveness of preventive strategy is mainly focused on avoiding the known local and systemic risk factors. The few studies that evaluated the effectiveness of preventive dental treatments exhibited great variability (Bonacina et al., ; Dimopoulos et al., ; La Verde et al., ; McGowan, McGowan, & Ivanovski, ; Mücke et al., ; Ripamonti et al., ; Sim et al., ; Vandone et al., ). Generally speaking, our institutional preventive dental protocol is in agreement with those proposed by several authors in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the effectiveness of preventive strategy is mainly focused on avoiding the known local and systemic risk factors. The few studies that evaluated the effectiveness of preventive dental treatments exhibited great variability (Bonacina et al., ; Dimopoulos et al., ; La Verde et al., ; McGowan, McGowan, & Ivanovski, ; Mücke et al., ; Ripamonti et al., ; Sim et al., ; Vandone et al., ). Generally speaking, our institutional preventive dental protocol is in agreement with those proposed by several authors in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] On the other hand, the concept of at-risk patients is hindered by the difficulty in establishing risk factors. 47 Our study has several limitations. Due to the limited literature available regarding non ARs-induced MRONJ, it was not possible to analyse these subsets of drugs.…”
Section: Discussionmentioning
confidence: 91%
“…In the case of PD, risk factors are well characterized but in the case of MRONJ these remain in an ongoing debate . McGowan et al recently performed a systematic review on this matter identifying 39 different systemic diseases, 14 medical and 11 dental risk factors, thereby elucidating the complexity of this outcome . The close connection between PD and diseases which are commonly managed with ARs, independent of their consumption, and which tend to be either cancers —that particularly favour bone metastasis—, or osteoporosis, has recently been reported in observational studies, building a web of intrigue .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that periodontal disease is a significant triggering factor for the development of MRONJ (McGowan et al, ; Yamazaki et al., ). This possibility is of special importance in patients who receive denosumab, given in a published series, most cases of ONJ developed spontaneously, without any known triggering event like dentoalveolar surgery, ill‐fitting dentures or local trauma (Yarom et al., ).…”
Section: Discussionmentioning
confidence: 99%